Long-term remission of impaired glucose tolerance in the finnish diabetes prevention study - Uusitupa, Matti; Valtanen, Mikko; Lindström, Jaana; Tuomilehto, Jaakko (Elsevier, 2026)
Aims
Lifestyle interventions induce remission in people with type 2 diabetes (T2D) and those with impaired glucose tolerance (IGT). We examined the long-term remission of IGT in the participants of the Finnish Diabetes Prevention Study and evaluated factors predicting remission during extended follow-up.
Methods
505 participants were included in analyses. The median duration of lifestyle intervention was four years, and follow-up lasted up to 18 years. Remission was defined as normoglycaemia (fasting plasma glucose < 5.6 mmol/L, 2-h post-load glucose < 7.8 mmol/L, HbA1c < 39 mmol/mol). We examined predictors of remission (weight, fat distribution, physical activity, diet, and insulin sensitivity and insulin secretion based on repeated oral glucose tolerance tests).
Results
Remission rates were 32% at least once, 13%, 12%, and 11% at year 1, year 3, and the first post-intervention follow-up visit (median 5 years, range 4 – 8 years). Short-term predictors of remission included weight loss, reduction in waist circumference, higher intake of fibre and lower intake of saturated fats, physical activity, enhanced insulin sensitivity, and recovery of insulin secretion. In the longer term, only insulin secretory and sensitivity indices were associated with remission.
Conclusion
IGT may be normalised in the long term through weight loss and healthier lifestyles choices.